Significance of Apoptosis in the Process of Tumorigenesis in Colorectal Mucosa and Adenomas in FAP Patients - Hildegard Weiß; Karl‐Heinz Jacobasch; Wolfgang Haensch; Brigitte Streller; Brigitte Hieke (Analytical Cellular Pathology)
The relation between proliferation and apoptosis was studied in colorectal mucosal biopsies (N=41), tubular adenomas (TA) (N=104) and tubulovillous adenomas (TVA) (N=34) from 37 FAP patients. Proliferative activity was determined by cell cycle distribution analysis. In addition, transcriptional capacity was determined by chromatin in situ testing. For both, DNA flow cytometry was used. Cycling cells were identified by immunohistochemical staining with monoclonal antibody Ki67. The existence of subdiploid apoptotic cells was derived from DNA and/or DNA/protein patterns. In a follow‐up group, the mucosa is characterised by a balance between proliferation (S % + G2M % = 19) and apoptotic cells (% = 17). The percentage of Ki67 positive cells (16%) corresponds to the percentages mentioned above. In TA, the amount of apoptotic cells remains unaltered, in TVA it decreases to 8%. At the same time, the percentage of Ki67 positive cells increases significantly in both TA and TVA (39%, 42%). With patients who underwent surgery due to clinical signs without histological evidence for malignancy, apoptotic cells in TA continue to decrease significantly (9%), without any changes in cycling cells. Only in the carcinoma‐bearing bowel, cycling cells increase to 52%. Here, the percentage of apoptotic cells in TVA reaches the lowest level (5%). A connection between proliferation and apoptosis was observed in mucosa and TVA. The process of tumorigenesis is characterised by a stepwise increase in resistance to apoptosis followed by an increase in cycling cells.